2021
DOI: 10.1186/s12913-021-07135-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity of diagnoses and procedures in Japanese dental claims data

Abstract: Background Dental claims data have been used for epidemiological studies without establishing the validity of the recorded diagnoses or procedures. The present study aimed to examine the accuracy of diagnoses, procedures, operation time, and the number of teeth recorded in dental claims data. Methods We reviewed the charts of 200 patients who visited and 100 patients who were hospitalized in the Department of General Dentistry, Orthodontics, and Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Fifth, we have not conducted quality checks of data from the NDB. However, studies examined the validity of data from NDB in Japan using sensitivity analyses, and showed that the recorded medical and dental diagnoses and procedures were useful in research using the administrative data [ [23] , [24] , [25] ].…”
Section: Limitationmentioning
confidence: 99%
“…Fifth, we have not conducted quality checks of data from the NDB. However, studies examined the validity of data from NDB in Japan using sensitivity analyses, and showed that the recorded medical and dental diagnoses and procedures were useful in research using the administrative data [ [23] , [24] , [25] ].…”
Section: Limitationmentioning
confidence: 99%
“…Full‐text articles of 42 studies were retrieved, and six were excluded because they compared aggregate data, validated self‐report questionnaires using claims data as a reference standard, were review articles, were aimed at refining the cancer registry and not for research purposes, did not report case‐defining methods, or did not report a reference standard 12,19–23 . There were 36 eligible studies, including 29 studies 8,10,11,13,24–48 that validated administrative data using an external reference standard and seven studies 9,49–54 that validated administrative data using other data within the same database.…”
Section: Resultsmentioning
confidence: 99%
“…Following previous validation studies, we defined diagnosis based on chart reviews as the reference standard 11,13,19,20. Because the quality of the descriptions in the charts affects the quality of the chart reviews, we took 2 measures.…”
Section: Discussionmentioning
confidence: 99%